Pipeline Insulation Analysis of Alpha Type Stirling Engine Generator Phase Angle 180° - Rina Lusiani; Erny Listijorini; Aswata; Dhimas Satria (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2021)
This research is a development of previous research, where in the previous research, a design innovation was carried out on an alpha-type stirling engine by making the phase angle to 180o, with the aim of reducing the effect when the cold cylinder is compressed, because the phase angle currently used is (90o) with disadvantages, namely the cold cylinder is perpendicular to the top, so that the compression process against gravity. But in previous studies, the generator pipe was too long, causing a lot of energy or heat loss (heat loss) so that the compression speed was small. So that in the research, innovated and analyzed the pipe insulation of alpha-type stirling engine generators, alpha-type stirling engines, 180o phase angle. The research method used is to use the thermodynamic approach with Schmidt theory and the theory of the ideal cycle stirling engine. while the simulation is done using the Ideal Stirling Cycle Calculator. Results investigated shows that providing insulation on the generator pipes of an alpha-type stirling engine for an alpha-type stirling engine with a 180o phase angle is proven to reduce a lot of energy or heat loss (heat loss) due to too long generator pipes, with a heat loss value ratio of 226.66 W for the pipe. generator that uses insulation whose value is smaller than the value of the heat loss when the generator pipe without using isocation is 1,584.12 W.